The Ghost of Disruption: Preventing Business Death with Organizational Culture and Engaging Artificial Intelligence - Primadona Primadona; Dyah Eko Setyowati; Duta Mustajab; Yudith Dyah Hapsari; Muhammad Taufan Ashshiddiqi (International Journal of Artificial Intelligence Research, 2022)
Organizational Identity (OI) as part of organizational culture refers to Organizational Change in organizational characteristics which in the eyes of its members are the center of the organization's character or "self-image". These characteristics distinguish the organization from other organizations of similar nature, and are seen as having continuity, especially towards the current era of disruption. The concept of organizational identity (OI) is of great interest to researchers for the simple reason that OI fits well with those who work in organizations. In the context of dynamic organizational transition in the era of disruption with artificial intelligence, OI has a very strong relationship. This study aims to conduct a systematic literature review on anthropomorphized organizational identity to offer new and important insights into how organizations engage organizational members to think, feel, and behave; unique organizational character, and the target of anthropomorphism will have a very significant impact, especially with the presence of artificial intelligence Researchers are able to carry out in-depth analysis and arrive at definite results because the data is obtained from academic publications and books containing references to organizational identity and organizational culture in the era of disruption.